Advances in the prevention and treatment of dementia. Issue 12 (December 2016) - Robinson, Ann
Abstract : There are currently no disease‐modifying therapies for dementia; existing licensed drugs offer symptomatic treatment only. This article explores recent developments in the search for more effective interventions for the prevention and treatment of Alzheimer's and other forms of dementia.